Hybrid coworking spaces for remote workers: The role of cafés and Discord channels as a unified community hub - Syamsiyah, Nur (Jurnal Sosiologi Dialektika, 2025)
Remote work has become increasingly popular in recent years, particularly following the global shift in work dynamics due to the COVID-19 pandemic. Such situations lead to new challenges in maintaining social connections and productivity among workers. Therefore, this study examines how hybrid coworking spaces, including cafés and Discord channels, function as community hubs for remote workers. Using a qualitative approach, the researcher conducted digital ethnography over six months (June-November 2023) on a coworking community for remote workers in Surabaya, Indonesia. In-depth interviews with eleven remote workers were also conducted. The findings show that cafés provide a social and productive environment as it gives remote workers a balance of focus and casual interaction. Discord channels further support this by creating a virtual coworking space that facilitates continuous communication, collaboration, and emotional support. The hybrid coworking spaces then creates a unified community hub that help reduce loneliness and build social connections among remote workers. This approach not only increases workers’ productivity but also enhances emotional well-being. It provides remote workers with both social energy and flexibility. The study concludes that the integration of physical and digital spaces can form a sense of community which supports remote workers in maintaining motivation and connection.